Reason, Justification, and Contractualism: Themes from Scanlon - Stepanians, Markus; Frauchiger, Michael; Forst, Rainer; Mantel, Susanne; Nagel, Thomas; Olsaretti, Serena; Parfit, Derek; Scanlon, T. M; Stemplowska, Zofia (Lauener library of analytical philosophy, 2021)
Frontmatter -- Brief Book Overview -- Acknowledgments -- Table of Contents -- Instead of an Introduction: Scanlon’s Project -- Deontological Communitarianism. Laudation for Thomas M. Scanlon -- Contractualism and Justification -- Justification Fundamentalism: A Discourse-Theoretical Interpretation of Scanlon’s Contractualism -- On How to Explain Rational Motivation: Where Internalism and Externalism Meet -- Moral Reality and Moral Progress -- Equality of Opportunity and Justified Inequalities: How the Family Can Be on Equality’s Side -- Improving Scanlon’s Contractualism -- Substantive Responsibility and the Causal Thesis -- Responses to Forst, Mantel, Nagel, Olsaretti, Parfit, and Stemplowska -- Words of Thanks -- Contributors -- Index